Global hotspots and trends of nutritional supplements for sick populations from 2000 to 2024 - Shi, Chaofan; Liu, Haitao; Fu, Te; Li, Yuanquan; Zhao, Haichang; Liu, Feiyue (Frontiers in Nutrition, 2025)
BackgroundNutritional supplements (NS) can help patients by providing various nutrients such as essential vitamins and minerals, helping to prevent and recover from diseases. This study provides a broad overview of the field of NS for sick people through bibliometrics and visualization analysis, to analyze the status and development dynamics, explore the popular research questions and directions, and reveal the development trends and research frontiers.MethodsWe searched the Web of Science Core Collection databases for literature related to NS for diseased populations from 2000 to 2024. A total of 1,550 articles were included in the analysis after screening. Analyses performed using CiteSpace and VOSviewer software.ResultsThe field of NS for the sick population has witnessed an overall rapid growth in the number of publications, which is divided into three phases: 2000–2008 was the exploratory phase, 2009–2017 was the sustained development phase, and 2018 to date is in the rapid development phase. Research focuses on dietary supplementation, oxidative stress, in vitro injections, development, antioxidant activity, double-blind trials, lipid supplements, functional foods, the health of diseased populations, and the risks of NS.ConclusionDifferent supplements each possess unique benefits and should be chosen according to the type of disease to ensure they contain the corresponding nutrients. Vitamin supplements are widely mentioned among patient populations across the globe. Future trends may focus on applying nutritional supplements in gut microbiota and bioactive compounds. Researchers frequently mention the application of NS in women, infants, and children. It should continue to be monitored and optimized in the future to enhance its therapeutic effects, thereby accelerating patients’ recovery and improving their quality of life.